The Role of Dietary and Lifestyle Factors in the Formation of Premature Ovarian Insufficiency - Ojo, Oluwafemi Adeleke; Ogundele, Deborah Olayinka; Soyinka, Tenifayo Oluwatamilore; Rotimi, Damilare Emmanuel; Ogunlakin, Akingbolabo Daniel; Iyobhebhe, Matthew; Ojo, Adebola Busola; Nwonuma, Charles Obiora; Alejolowo, Omokolade Oluwaseyi; Evbuomwan, Ikponmwosa Owen (Nigerian Institution of Professional Engineers and Scientists, 2026)
Premature ovarian insufficiency (POI) is a complex medical condition characterized by the early depletion of ovarian follicles, leading to diminished ovarian function before the age of 40. This condition can manifest in various ways, including early menopause, which is defined as the cessation of menstrual periods for a full year, and a significant reduction in fertility potential. The consequences of POI can be profound and deeply affect a woman's physical and emotional health, as it often leads to symptoms commonly associated with menopause, such as hot flashes, night sweats, and mood changes. Additionally, women with POI may face challenges related to infertility, which can have a significant psychological impact. Recent research has begun to shed light on the multifaceted nature of POI, revealing that oxidative stress plays a crucial role in its development and progression. Oxidative stress refers to an imbalance between free radicals, which are unstable molecules that can cause cell damage, and antioxidants, which help neutralize these harmful substances. Excessive oxidative stress can lead to the premature aging of ovaries and a reduction in the quality and quantity of ovarian follicles. Moreover, emerging evidence suggests that lifestyle factors, particularly dietary habits, can significantly influence the risk of developing POI. A diet rich in antioxidants, vitamins, and minerals may help mitigate oxidative stress, potentially protecting ovarian function. For instance, foods high in omega-3 fatty acids, such as fatty fish, as well as fruits and vegetables packed with antioxidants, can contribute to overall reproductive health. Integrating a balanced diet that prioritizes these nutrient-rich foods may not only support ovarian health but also delay the onset of menopause. In addition to dietary considerations, other lifestyle interventions, including regular physical activity and stress management techniques, can also play a role in reducing the risk of POI. Regular exercise has been shown to improve overall health and may help regulate hormonal balances that are vital for reproductive function. Stress management through mindfulness, yoga, or other relaxation techniques can further support hormonal health and enhance overall well-being. This review underscores the critical interplay between oxidative stress and lifestyle factors in the context of premature ovarian insufficiency. By recognizing the impact of diet and lifestyle choices, targeted interventions can be developed to help reduce or even delay the onset of POI. This proactive approach could empower women to take charge of their reproductive health, promoting better outcomes and enhancing their quality of life as they navigate the challenges associated with early ovarian insufficiency. Ultimately, a deeper understanding of these factors provides a pathway for more effective prevention and management strategies for those at risk.